Analisis Kebutuhan Garam Pengasinan Di Kecamatan Sungailiat Kabupaten Bangka - Muhammad Fiqry Pratama; Andi Gustomi; Fika Dewi Pratiwi (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
Fish production in the Bangka Belitung Islands Province has increased from 203.81 tons in 2014 to 228,520 tons in 2018. This large amount of production has led to an increase in household businesses managing the fishery sector. One of the processing in the fisheries sector is the management of salted fish. This study aims to analyze the need for salt and develop a strategy for developing salted fish in Sungailiat District. This research will be carried out in September 2021 in Sungailiat District, where there is a salted fish processing business. The data collected in this study are primary data and secondary data. Primary data is data obtained directly from the source, the method used in analyzing the data uses SWOT analysis through interviews. The amount of salt used in salting in Sungailiat sub-district ranges from 50-3000 kg per month or 248.4 tons of salt per year with prices ranging from Rp. 1700 – IDR 5000/Kg. The salt used is obtained from shops in the market and also collectors. The strategy for developing a fish salting business in Sungailiat Subdistrict is to build a salt factory or place to make salt in the area as well as conduct training and counseling as well as providing capital assistance to salted fish business actors so that the business can grow rapidly. Keywords:Pickling Salt, SWOT, Sungailiat